PROFESSIONAL MOBILITY AS DETERMINANT OF SOCIAL ADAPTATION AND CREATIVE SELF-REALIZATION OF TEACHER’S PERSONALITY IN THE CONDITIONS OF POSTGRADUATE EDUCATION - Bilyk, Nadia (Social work and education, 2019)
Today's professional requires being ready for constant updating of knowledge, objective growth, development of new information sources and technologies, prompt reaction to their changes. Therefore, it is an urgent need to ensure the training of qualified personnel who are capable for creative work, professional self-development, and introduction of science and information technologies, competitive and mobile in the labor market.Mobility is an integral part of the professional self-realization of teachers, through which aspire for success and flourish potential for creativity in pedagogical activities. Theoretical analysis of psychological and pedagogical studies revealed multidimensionality, versatility and professional importance of the phenomenon of “mobility”. Scientists have explored this concept in the following areas: the social readiness of the individual for change; grouping of personality traits needed to integrate professional development; ability to quickly master innovation, new skills; properties that determine the level of adaptability and competitiveness in the labor market.In this case, the issue of occupational mobility has become the subject of research by representatives of different fields of science studying this category in different formats. Economists, sociologists, philosophers, educators view professional mobility at an angle that is consistent with the tradition of their scientific schools, highlighting some of its aspects.As educational system is rapidly updated and developing, so the problem of professional development is facing the institution of postgraduate pedagogical education. We believe that a teacher’s professional mobility is a willingness to promptly implement the best ways to perform a variety of tasks within profession, to possess professional techniques and skills, and use them effectively for the purpose of performing any task. Therefore, it is advisable to consider professional mobility as a determinant of social adaptation and creative self-realization of the teacher, that is, effective response to the challenges of modern society. This is a kind of personal resource that underlies pedagogical activity.